Cannabis law reform in Japan$Dgoing with or against the tide? - Brewster, David (Law and culture in Japan, 2025)
Purpose: The purpose of this chapter is to explore and explain recent legal reforms concerning cannabis in Japan. Methodology: Documentary data, including committee reports, explanatory documents, and a published insider account of policy processes, along with statistical data concerning the enforcement of drug laws and self-reported drug use are utilized to piece together the reforms. The chapter also draws upon policymaking and governance literature to explain the dynamics of the policy processes. Findings: Recent reforms of laws concerning cannabis in Japan reflect both a loosening and tightening of approaches. These seemingly contradictory patterns need to be understood in the context of, and relation to, international movements in cannabis policy. Although the liberalization of cultivation and use of cannabis for medical purposes reflects how discourse, evidence, and approaches emanating from overseas have been partially internalized and accepted, the criminalization of non-medical use is reflective of the ways domestic authorities in Japan continue to try and maintain a prohibitive approach despite policy liberalization elsewhere. Value: This chapter provides an original analysis of the most recent reforms to cannabis laws in Japan, revealing the multifaceted and competitive nature of drug policy and how different policy actors have adapted and reacted to external pressures.